Exploring Facial Structure Variability and Freeway Space in Fully Dentate Adults: Findings from Clinical Study - Aradya, Anupama; Chowdhary, Ramesh; Ravi M B,; Sree Shyla H S,; Sravani, Koduru; Ranganatha, Narahari (Medical Research and Its Applications Vol. 8, 2024)
Aim: This study aims to assess the average freeway space among fully dentate individuals during rest and occlusion across different facial forms. Background: The freeway space (FWS), or interocclusal distance, is determined by the balance between the elevator and depressor muscles attached to the mandible, and the “elastic” nature of the surrounding soft tissue in natural dentition. Lower one-third of the face can have far-reaching effects on facial aesthetics, not only on the peri-oral areas but also on the entire face. Mandibular posture greatly depends on head posture. Materials and Methods: Fifty subjects from each of three facial form groups- square, taper, and oval- with a complete set of maxillary and mandibular arch teeth, aged between 25 to 40 years, were included. Equal numbers of males and females were represented in all groups. Vertical height at rest and occlusion was recorded using standardized procedures and freeway space (FWS) was measured Results: Statistical analysis of the collected data revealed mean and median values for each facial form: square (3, 2.32), taper (2.62, 2), and ovoid (2.68, 2), respectively. No significant differences were observed between these readings (P < 0.05). However, 9% of the individuals exhibited the FWS range of 5–6 mm with measurements ranging from 1 and 7 mm, respectively. Notably, the majority (56%) of the square facial form subjects displayed an FWS range of 3–4 mm. Conclusion: This study provides insights into the average inter-arch space across various facial forms, indicating a measurement typically exceeding 3–4 mm. The future prospective of this study is that evaluating the FWS in edentulous patients with an increased number of subjects would definitely increase the clarity.